Notes on Rural Education in Colorado do Oeste/Rondônia: notes of a literate peasant - William Kennedy Do Amaral Souza; Raiane Agustinho Lopes; Vanessa Campos Moraes; Marcos Antonio Oliveira Rodrigues (Universidade Federal do Norte do Tocantins, 2018)
This paper will address concerns about the dichotomy between Education in the countryside and Rural Education. Based on the theoretical reference reading, we decided to confront what we know of the Brazilian educational system, with the reality we experienced and, in addition, to confront the official discourse of plural education with the desire and need of social movements for a more dignified education. The social movement chosen for our analysis was the Small Farmers' Movement (MPA), as it is a movement of wide reach and support in our region. For this we elect a person who is part of the movement to carry out a semi-structured interview. The interviewee is graduated in a course directly involved with Education which also gives him theoretical background to discuss this topic. According to the data collected the people of the MPA believe in a better educational system, and this improvement goes through the dialogue between the State and Social Movements. In the case of the MPA, this dialogue has as its central idea the valorization of the peasant culture within the school environment and, the guarantee of the maintenance of the rural schools can thus help to reduce the rural exodus and consequently to improve the quality of life.